Studying the relationship between human papillomavirus (HPV) and breast cancer in Iraqi patients (Eurasian Medical Research Periodical, 2023)
Viruses such as HPV have been identified in benign and cancerous breast tissue and as etiologies. Breast cancer has been considered, but there is controversial information about viral induction of breast cancer. The purpose of this study Investigation of the presence of human papillomavirus in Iraqi breast cancer patients.